2009
DOI: 10.1111/j.1532-849x.2009.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Bone Physiology: Demonstration of Vitamin D Deficiency in an Implant Osseointegration Rat Model

Abstract: The effect of vitamin D insufficiency significantly impairing the establishment of Ti6Al4V implant osseointegration in vivo was unexpectedly profound. The outcome of Ti-based endosseous implants may be confounded by the increasing prevalence of vitamin D insufficiency in our patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(104 citation statements)
references
References 30 publications
3
93
0
8
Order By: Relevance
“…Thus, our vitamin D deficiency model was successfully developed. Previous studies demonstrated that basal levels of vitamin D in rats range from 12 to 20 ng/mL [23], [24]. Moreover, Ismail et al [25] using a 6-week-vitamin D deficiency model in Wistar rats showed that the levels of 25(OH)D were approximately 1.0 ng/mL in vitamin D-deficient animals while control group presented around 20.0 ng/mL.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, our vitamin D deficiency model was successfully developed. Previous studies demonstrated that basal levels of vitamin D in rats range from 12 to 20 ng/mL [23], [24]. Moreover, Ismail et al [25] using a 6-week-vitamin D deficiency model in Wistar rats showed that the levels of 25(OH)D were approximately 1.0 ng/mL in vitamin D-deficient animals while control group presented around 20.0 ng/mL.…”
Section: Discussionmentioning
confidence: 97%
“…The causes of early implant failure are not fully clarified and an association between vitamin D and dental implant osseointegration has not been investigated properly [8, 1316]. Some recent animal studies in rodents demonstrated a relationship between vitamin D supplementation and an increased bone to implant contact/volume after implant placement [14, 34, 35]. Mengatto et al demonstrated an impaired osseointegration in vitamin D-deficient rats [36].…”
Section: Discussionmentioning
confidence: 99%
“…The high social and health relevance of the phenomenon of osseointegration is clearly observed by the innumerous studies on bone physiology and repair available in literature (Robiony et al, 2008;Kelly et al, 2009), as well as the advanced technology in search of biomaterials (Cowan et al, 2005) in order to promote local bone formation, and make possible the rehabilitation of partially or totally deficient edentulous jaws using dental implants (Aghaloo and Moy, 2007). Although autogenous bone graft is still considered the gold standard material for bone reconstruction, a second surgical approach and morbidity of donor site are the main disadvantages (Cricchio and Lundgren, 2003;Chiapasco et al, 2006).…”
Section: Introductionmentioning
confidence: 97%